2021
DOI: 10.3390/cryst11111437
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Vacuum Diffusion Bonded Zr-4 Alloy Joint

Abstract: The development of welding technology for zirconium alloy has great significance on the safety, stability, and reliability of the operation of the nuclear reactor. In this work, vacuum diffusion bonding of Zr-4 alloy was studied at the diffusion temperature ranging from 760 to 820 °C with holding times of 30–90 min. The effects of diffusion bonding temperature and holding time on the interfacial microstructure and mechanical properties of the diffusion bonded Zr-4 alloy joints were investigated in detail, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A small randomized controlled trial compared the effect of Ciprofoxacin and Mesalazine in patients with mild to moderate CD and observed complete remission with Ciprofloxacin [95]. Another randomized trial showed early benefits of antibiotics in 213 patients receiving either Clarithromycin, Rifabutin, or Clofazimine, with no significant difference in the relapse rates were noted in follow-up [96]. Antibiotic therapy is also used to prevent postoperative recurrence of CD and in treatment of complications of CD like perianal abscess and fistula.…”
Section: Antibiotic Therapymentioning
confidence: 99%
“…A small randomized controlled trial compared the effect of Ciprofoxacin and Mesalazine in patients with mild to moderate CD and observed complete remission with Ciprofloxacin [95]. Another randomized trial showed early benefits of antibiotics in 213 patients receiving either Clarithromycin, Rifabutin, or Clofazimine, with no significant difference in the relapse rates were noted in follow-up [96]. Antibiotic therapy is also used to prevent postoperative recurrence of CD and in treatment of complications of CD like perianal abscess and fistula.…”
Section: Antibiotic Therapymentioning
confidence: 99%